Conversion Technique From 2D To 3D Model For A Shape-Changing Aircraft Slat Mechanism - Ismail, Mohammad Hazrin (2018)
Airframe noise reduction is a topic being investigated for the well-being of people living close to airports. This type of noise can occur between the high-lift systems and main body of the airfoil. The proposed shape-changing mechanism is an alternative to reduce airframe noise by eliminating the gap during deployment of the high-lift systems. This work presents a new design of the 30P30N wing, which focusses on installing a shape-changing slat into the systems. This work applies a chain of rigid body wing segments connected by revolute and prismatic joints that are capable of approximating a shape change defined by a set of morphed slat design profiles. The [C M q slat segment design was created as a result of optimised segmentation process using the Shapechanger software where C is a constant curvature segment that may change length, while M is a mean segment of fixed length. The XY data are exported into CATIA software through macros command. To achieve a single degree of freedom (DOF), a building-block approach is employed to mechanise the fixed-end shape-changing chain by using Geometric Constraint Programming as an effective method to design the mechanism. Lastly, a small scale threedimensional model is developed to mechanise the mechanism driven by a single actuator. Related results showed that the shape-changing airfoil that deploys without a gap between the slat and main body, has a pressure coefficient of around -2.0 whereas the conventional one with gap hovers at -1.0. In addition, the values of Sound Pressure Level (SPL) were improved by maintaining below 100 dB near the slat portion of the airfoil.